Pelatihan dan Kepemimpinan Visioner dalam meningkatkan Kreativitas Pegawai di Kalimantan Tengah - Sambung, Roby (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 2 Tahun 2020DO - 10.24843/MATRIK:JMBK.2020.v14.i02.p04, 2020)
The aim of this paper to explain the influence of leadership training in visionary leadership, on the creation of employee creativity, and the role of sharing knowledge as the moderating variable. The respondents consist of   50 echelon III officials from 30 government organizations of Central Kalimantan taking part in the new pattern of leadership training and education. Variant base SEM is used to analyze the data. The results show visionary leadership mediates the relationship between leadership training and employee creativity. Knowledge sharing is proven to moderate the relationship between visionary leadership and employee creativity. This research contributes to the development of leadership theory in government organizations, this shows that leaders with a visionary leadership style are able to increase employee creativity in the workplace, but it depends on the knowledge sharing behavior of the leader